Das Potenzial der kleinen Stadt Litomysl. Baukultur, Politik, Stadterneuerung. The potential fo the small city of Litomysl. Building culture, policy, urban regeneration. - Aicher, Florian (Ed. Detail, 2019)
Die tschechische Kleinstadt Litomysl zählt zum Unesco-Welterbe dank ihrem beeindruckenden Marktplatz und ihrem Renaissanceschloss. Von architektonischer Ambition getragen, entfaltet Litomysl seit 1989 einen Aufschwung, der in zahlreichen herausragenden Interventionen sichtbar wird. Vom Neubau bis Umbau, vom Stadtraum bis zur Stadtmöblierung, vom kleinen Eingriff bis zum selbstbewussten Statement entfaltet sich ein breites Spektrum. Das Buch thematisiert die Potenziale der Stadt, die politische Dimension von Architektur und Tendenzen neuer tschechischer Architektur. Essays und Interviews ergänzen die Vorstellung ausgewählter Projekte. Das Spektrum deckt Interventionen im Stadtraum und Grünanlagen, Pflege der Bausubstanz und Neubau, öffentliches und privates Bauen, Bauwerk und Interieur ab.

How is it possible to keep the immense deposits of raw materials in buildings "active" and realise environmentally sustainable buildings in the long term? Besides "sufficiency, consistency and efficiency", this goal implies the intelligent use of resources, the recyclability of structures, circular construction methods that reuse decommissioned materials, in short "urban mining". This requires a rethink in planning and execution, thus posing a great challenge for architects and engineers. The Manual of Recycling provides the necessary expertise for the associated paradigm shift in construction. In addition to successful project examples, this comprehensive and detailed guide provides in-depth explanations on calculation methods and tendering aspects: recyclable construction, urban mining - resource city and buildings, structures that can be dismantled; design and design methodology in the life cycle, detailed guide of relevant construction component connection.
Keywords: Stadtgeschichte; Architektur; Weltkulturerbe; Marktplatz; Historisches Gebäude; Stadtentwicklung; Neubau; Umbau; Stadtraum; Stadtmöblierung